A branching scheme based on First-Break-Then-Schedule decomposition - Dirk Briskorn; Andreas Drexl (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2007)
Single round robin tournaments are a well known class of sports leagues schedules. We consider leagues with a set T of n teams where n is even. Costs are associated to each possible match. The goal is to find the minimum cost tournament among those having the minimum number of breaks. We pick up structural properties of home-away-pattern sets having the minimum number of breaks. An branching idea using these properties is developed in order to guide branching steps on the first levels of a branch-and-bound tree in order to avoid nodes corresponding to infeasible subproblems.
Keywords: 650; Sports league scheduling; round robin tournaments; home-away-pattern set; break; branch-and-bound; Sport; Scheduling-Verfahren; Branch-and-Bound; Theorie